2010
DOI: 10.1038/sj.bjc.6605608
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in plasma of patients with gastric cancers

Abstract: BACKGROUND: We examined plasma microRNA (miRNA) concentrations from patients with gastric cancers (GCs) to assess their clinical application for diagnosing and monitoring diseases. METHODS: We initially investigated the appropriateness of plasma miRNA assay, and then compared plasma miRNA results with the expressions in cancer tissues from eight GC patients, and also compared plasma miRNAs between pre-and post-operative paired samples from 10 GC patients. Then, plasma miRNAs (miR-17-5p, miR-21, miR-106a, miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
425
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 566 publications
(458 citation statements)
references
References 31 publications
27
425
2
4
Order By: Relevance
“…In Zheng's study, patients with gastric cancer display a significantly higher level of miR-21 in peripheral blood than those from controls. The miR-21 level was associated with the tumor node metastasis (TNM) stage, tumor size and tissue categories (Tsujiura et al, 2010). Wang and his colleagues revealed that serum miR-21 was elevated in patients with non-small cell lung cancer, and high serum miR-21 was significantly correlated with tumor-node metastases stage, lymph node metastasis, and shorter survival .…”
Section: Discussionmentioning
confidence: 99%
“…In Zheng's study, patients with gastric cancer display a significantly higher level of miR-21 in peripheral blood than those from controls. The miR-21 level was associated with the tumor node metastasis (TNM) stage, tumor size and tissue categories (Tsujiura et al, 2010). Wang and his colleagues revealed that serum miR-21 was elevated in patients with non-small cell lung cancer, and high serum miR-21 was significantly correlated with tumor-node metastases stage, lymph node metastasis, and shorter survival .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the exploration of novel and feasible biomarkers for prognosis is essential for improving outcomes in GC patients. Currently, growing evidences have disclosed that the expressions of miRNAs originating from tumor tissues are detectable in blood samples by dissociation of cancer cells or transformation via exosome in cancer patients, and several miRNAs expressions in blood are shown to be correlated with the risk and clinicopathological features of various cancers 69, 70, 71. In this present study, we found that high expressions of 4 circulating pro‐angiogenic miRNAs including miR‐17‐5p, miR‐18a, miR‐20a, and miR‐210 were independent predictive factors for worse DFS and OS in GC patients; furthermore, the combination of these 4 circulating pro‐angiogenic miRNAs presented even better prognostic value for prognosis than individual one in GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,20,21 Most microRNAs studies on cancer and cardio-vascular diseases report microRNA concentrations from 1 fM to 1 pM. [22][23][24][25][26] With a detection limit of 50 aM and 570 copies and 6 orders of magnitude dynamic range without sample amplification, our device holds promise for point-of-care diagnosis of infectious diseases, cancers, brain injuries, and other diseases from short DNA fragments and microRNAs.…”
mentioning
confidence: 99%